Oxidation State Specific Generation of Arsines from Methylated Arsenicals Based on L- Cysteine Treatment in Buffered Media for Speciation Analysis by Hydride Generation - Automated Cryotrapping - Gas Chromatography-Atomic Absorption Spectrometry with the Multiatomizer - Matoušek, Tomáš; Hernández-Zavala, Araceli; Svoboda, Milan; Langrová, Lenka; Adair, Blakely M; Drobná, Zuzana; Thomas, David J; Stýblo, Miroslav; Dědina, Jiří (Spectrochimica acta. Part B, Atomic spectroscopy, 2008)
An automated system for hydride generation - cryotrapping- gas chromatography - atomic absorption spectrometry with the multiatomizer is described. Arsines are preconcentrated and separated in a Chromosorb filled U-tube. An automated cryotrapping unit, employing nitrogen gas formed upon heating in the detection phase for the displacement of the cooling liquid nitrogen, has been developed. The conditions for separation of arsines in a Chromosorb filled U-tube have been optimized. A complete separation of signals from arsine, methylarsine, dimethylarsine, and trimethylarsine has been achieved within a 60 s reading window. The limits of detection for methylated arsenicals tested were 4 ng l(-1). Selective hydride generation is applied for the oxidation state specific speciation analysis of inorganic and methylated arsenicals. The arsines are generated either exclusively from trivalent or from both tri- and pentavalent inorganic and methylated arsenicals depending on the presence of L-cysteine as a prereductant and/or reaction modifier. A TRIS buffer reaction medium is proposed to overcome narrow optimum concentration range observed for the L-cysteine modified reaction in HCl medium. The system provides uniform peak area sensitivity for all As species. Consequently, the calibration with a single form of As is possible. This method permits a high-throughput speciation analysis of metabolites of inorganic arsenic in relatively complex biological matrices such as cell culture systems without sample pretreatment, thus preserving the distribution of tri- and pentavalent species.